2017
DOI: 10.5897/ajar2015.10763
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on cotton production in Burkina Faso

Abstract: This paper evaluated the impact of climate change on cotton production in Burkina Faso. An econometric analysis resulted in identifying the major factors influencing cotton yields and evaluating the likely effects of future climate change. The results of our study regarding the potential impact of future climate change on cotton yield indicated that further increases in global temperature would significantly reduce the yield of cotton. Future changes in rainfall would also affect cotton production, but compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 24 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Analysis by [55] revealed that daily minimum temperatures will increase more rapidly than daily maximum temperatures leading to the increase in the daily mean temperatures and a greater likelihood of extreme events and these changes could have detrimental effects on grain yield. If these changes in temperature are expected to occur over the next 30 years then understanding the potential impacts on plant growth and development will help develop adaptation strategies to offset these impacts [56,57].…”
Section: Impact Of Climate Change On Crop Productionmentioning
confidence: 99%
“…Analysis by [55] revealed that daily minimum temperatures will increase more rapidly than daily maximum temperatures leading to the increase in the daily mean temperatures and a greater likelihood of extreme events and these changes could have detrimental effects on grain yield. If these changes in temperature are expected to occur over the next 30 years then understanding the potential impacts on plant growth and development will help develop adaptation strategies to offset these impacts [56,57].…”
Section: Impact Of Climate Change On Crop Productionmentioning
confidence: 99%
“…Burkina Faso has a semi-arid tropical climate divided into three climatic zones: Sahelian in the North, Sahelo-Sudanese in the middle, Sudanese in the South (Abdoulaye et al, 2017). The Hauts Bassins region is located in the Sudanese climatic zone, the least hot and the wettest area.…”
Section: Study Settingmentioning
confidence: 99%
“…The annual mean relative humidity is about 80% in the south and 55% in the north (ASECNA, 2010). The climatic limiting factor for plant growth is rainfall which is generally tending to diminish with increasing variation between years for most West African countries (Kagoné, 2000;Adjolohoun, 2008;Diarra et al, 2017). These characteristics have to be taken into account in research and development programs so as to anticipate food and forage crises.…”
Section: Climate and Agro-ecological Zonesmentioning
confidence: 99%